Optimalisasi Pelaksanaan Pemantauan dan Evaluasi Kinerja Penyelenggara Pelayanan Publik (PEKPPP) di Puskesmas Gunung Anyar - Abiyyu Fawwaz Abrizam; Diana Hertati (Intitut Agama Islam Nasional Laa Roiba Bogor, 2024)
Optimizing the implementation of monitoring and evaluation of public service provider performance (PEKPPP) at Puskesmas Gunung Anyar is a crucial effort to enhance public health service quality. This study employs a qualitative approach with a case study method to delve into the subject. Data were gathered through in-depth interviews, observations, and document analysis. Findings indicate the necessity of efficient management information system integration and enhanced human resource capacity. Additionally, active community participation in the evaluation process is crucial to improve responsiveness and accountability of Puskesmas. The research results show that the implementation of monitoring and evaluation at the Gunung Anyar Community Health Center still faces various challenges, including limited human resources, lack of training, and minimal use of information technology. To overcome this obstacle, it is recommended to increase human resource capacity through regular training, develop an integrated management information system, and increase community participation in the evaluation process. Implementation of this strategy is expected to increase the effectiveness of performance monitoring and evaluation, which in turn will improve the quality of health services at the Gunung Anyar Community Health Center. This study provides important insights for policy makers in formulating better policies for managing health services at the Puskesmas level.